Tremor in progressive supranuclear palsy - Fujioka, Shinsuke (Parkinsonism Relat Disord, 2016)
INTRODUCTION: Tremor is thought to be a rare feature of progressive supranuclear palsy (PSP). METHODS: We retrospectively reviewed the database of the CurePSP brain bank at Mayo Clinic Florida to retrieve all available clinical information for PSP patients. All patients underwent a standard neuropathological assessment and an immunohistochemical evaluation for tau and α-synuclein. DNA was genotyped for the MAPT H1/H2 haplotype. RESULTS: Of the 375 PSP patients identified, 344 had a documented presence or absence of tremor, which included 146 (42%) with tremor, including 29 (20%) with postural/action tremors, 16 (11%) with resting tremor, 7 (5%) with intention tremor, 20 (14%) with a combination of different types of tremor, and 74 (51%) patients who had tremor at some point during their illness, but details were unavailable. The tremor severity of 96% of the patients (54/55) who had this data was minimal to mild. The probability of observing a tremor during a neurological examination during the patient’s illness was estimated to be ~22%. PSP patients with postural/action tremors and PSP patients with resting tremor responded to carbidopa-levodopa therapy more frequently than PSP patients without tremor, although the therapy response was always transient. There were no significant differences in pathological findings between the tremor groups. CONCLUSIONS: Tremor is an inconspicuous feature of PSP; however, 42% (146/344) of the PSP patients in our study presented some form of tremor. Because there is no curative therapy for PSP, carbidopa/levodopa therapy should be tried for patients with postural, action, and resting tremor.